Impact of Dividend Policy on Shareholders’ Wealth: A Study of Listed Non-Financial Institutions in Sri Lanka - Yogendrarajah, R.; Mithila, G.; Dilaxshana, S. (University of Vavuniya, 2022)
The dividend policy is one of the essential areas in corporate finance, and this study focuses on analysing the impact of firms’ dividend policy on shareholders' wealth. The companies listed on Colombo Stock Exchange (CSE), 67 non-financial companies, were selected using Stratified random sampling method, and data are collected from companies audited financial statements over the last five years from 2016 to 2020. Collected data are analysed using Correlation, Multi collinearity test, Unit root test and panel least squares regression analysis. Since the study aims to analyse the impact of dividend policy on shareholder wealth, explanatory variables of the study are considered as Dividend Per Share (DPS), Dividend Pay Out ratio (DPO), Dividend Yield (DY), the market share price is considered as an outcome variable and Firm Size (FS) and Financial Leverage (LEV) is used as the controlling variables on the relationship between dividend policy and shareholders wealth. Shareholders' wealth is measured by the market share prices of the firms. Panel least squares regression analysis resulted in approximately 53% of the variability in the share holders’ wealth being explained by the explanatory variables, and there is a significant positive relationship between DPS, FS and shareholder wealth of the company. On the other hand, at the same time, DY negatively impacted shareholders' wealth. Further, the study revealed an insignificant relationship between shareholder wealth and DPO and LEV of the firms. Hence, this study confirmed the dividend relevance theory, and in the Sri Lankan market context, DPS, FS and DY significantly impact shareholders' wealth. Further, the results of this study can be used by various parties, namely academicians, practitioners, policy makers and investors, for their future research to formulate and implement policies for the companies, especially when setting financial objectives, the companies can embed dividend policy to improve the shareholders’ wealth.
Keywords: Dividend Per Share; Dividend Pay-out; Dividend Yield; Market Price Per Share; Shareholders’ wealth